Strong summability of orthogonal expansions of summable functions. II - Lasuriya, R. A.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of strong summability of Fourier series in orthonormal systems of polynomialtype functions and establish local characteristics of the points of strong summability of series of this sort for summable functions. It is shown that the set of these points is a set of full measure in the region of uniform boundedness of the systems under consideration.